تعليم المفردات باستخدام "كاهوت" في المدرسة المتوسطة الإسلامية الحكومية باريتو الجنوبية، كالمنتان الوسطى - Lubis, Nurhayati Amanda (Maharaat Lughawiyyat: Jurnal Pendidikan Bahasa Arab, 2023)
The objectives of this study is to measure the effectiveness of using kahoot media in vocabulary learning in Junior High School Islamic South Barito, Cental Kalimantan in eighth grade.The research method used in this study is a quantitative approach with an experimental method with the type of Quasi Experiment Design. The data collection techniques in this study used tests (pretest and post-test), observation and questionnaires. And Data analysis using Independent Sample T-test. The results of this study can be concluded that The use of kahoot media is effective for vocabulary learning in Junior High School Islamic South Barito. Based on the T test = 8,0. The result is greater than the result in a significant 1% = 2.39012 and 5% = 1.67065 . This means that Ha is accepted and H0 is rejected. And the results of this test are accepted.